Postharvest forum launched - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
PhAction, a new worldwide forum, aims to raise the profile of postharvest research and development by fostering better links between all who have an interest in postharvest products. PhAction was established at the initiative of the Group for...